2019
DOI: 10.1016/j.comtox.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Computational models for the assessment of manufactured nanomaterials: Development of model reporting standards and mapping of the model landscape

Abstract: Highlights The transparent and systematic reporting of computational models facilitates their regulatory acceptance and use. A reporting format for physiologically based kinetic, toxicodynamic and environmental fate models was developed. The QSAR Model Reporting Format (QMRF) was adapted to describe QSARs for nanomaterials. The model documentation is stored in the publicly accessible JRC Data Catalogue. The model docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…In the past decade, a variety of data driven computational approaches, such as Quantitative Structure-Activity Relationship (QSAR) models and read-across approaches that use diverse machine learning methods, have been used to predict NM-related toxicity [ 10 , 148 ]. The goal of these methods is to map the material description and intrinsic/extrinsic physicochemical properties to the biological outcomes to identify NM properties of concern, and facilitate design of NM that avoid, reduce or modulate these properties [ 150 , 151 ]. Computational techniques provide additional benefits where specific descriptors or properties are not readily measurable, as they can derive these using chemistry- and physics-based materials modelling [ 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, a variety of data driven computational approaches, such as Quantitative Structure-Activity Relationship (QSAR) models and read-across approaches that use diverse machine learning methods, have been used to predict NM-related toxicity [ 10 , 148 ]. The goal of these methods is to map the material description and intrinsic/extrinsic physicochemical properties to the biological outcomes to identify NM properties of concern, and facilitate design of NM that avoid, reduce or modulate these properties [ 150 , 151 ]. Computational techniques provide additional benefits where specific descriptors or properties are not readily measurable, as they can derive these using chemistry- and physics-based materials modelling [ 148 ].…”
Section: Resultsmentioning
confidence: 99%
“…And as a matter of fact in silico models are the subject of intensive research and different computational models for nanomaterials have been reported (Lamon et al 2018). Among them, QSAR models (Fourches et al 2010;Puzyn et al 2011;Winkler et al 2013;Gajewicz et al 2015b;Pan et al 2016), read-across (Gajewicz et al 2015a(Gajewicz et al , 2017Gajewicz 2017a, b), neural network (Fjodorova et al 2017) or decision tree (Gajewicz et al 2018) classifications.…”
Section: Discussionmentioning
confidence: 99%
“…As the rule of thumb, model validation is performed by increasing the number of involved variables and assessing performance [26,27]. The ratio of (count of NMs)/(count of descriptors) has a cut-off value of 5 (Topliss ratio), which is recommended while regulating to avoid needless complexity, according to the parsimony principle [16,28]. The final number of QSAR descriptors should not exceed six, but when knowledge of the relevance of properties to nanotoxicity is limited, a large number of initial descriptors should be sought [29].…”
Section: Feature Selectionmentioning
confidence: 99%